Study on the Influence of Positive Learning Environment on Student Motivation and Achievement in Elementary Schools - Cikita Fadila; Harsono; Anatri Desstya (Postgraduate, University of Mataram, 2025)
A positive learning environment is an important factor in improving student motivation and achievement. This study aims to analyze the influence of the learning environment, both physical and social, on student motivation and achievement at SD GMIT Airnona 2 Kupang City. Using a quantitative approach with a census design, all 88 students in grades 4–6 were used as respondents. Data were collected through questionnaires and interviews. The results showed that a comfortable learning environment, positive social interactions, and teacher support contributed significantly to improving student motivation and achievement. These findings underline the need for improved facilities, teaching innovation, and parental involvement to create an optimal learning environment.